THE MARKETING CHANNEL OF FRESH FISH PRODUCTS AT SENDANG BIRU BEACH - Keppi Sukesi; Inggrida, Jedda Ayu (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2024)
Indonesia is one of the maritime countries that has a large coastal area where the area is around the beach that leads to the sea and to the land. One of the coastal areas that has a wealth of marine products is the Sendang Biru area located in Sumbermanjing Wetan District, Malang Regency, East Java. Sendang Biru beach is directly facing the Indian Ocean which has a long potential for abundant fishing. The informants obtained were 6 traders, this has been determined based on the criteria, namely female traders, working as fresh fish traders for at least 3 years, and selling various type of fish. There are four marketing channels that occur in Sendang Biru, based on the results of the interview, it was found that the first and fourth channels have better efficiency than other channels, this is because channels one and four are the shortest channels so that the price difference between fishermen and consumers is not high.